Психолого-педагогічна підготовка майбутніх викладачів професійно-технічних навчальних закладів: акмеологічний аспект - Сосницька, Наталя Леонідівна; Сосницкая, Наталья Леонидовна; Sosnytska, Natalia; Кривильова, О. А. (My University, 2017)
UK: У статті теоретично обґрунтовано акмеологічний вплив та супровід психологопедагогічної підготовки майбутніх викладачів професійно-технічних навчальних закладів: наведено сутність понять «акмеологічний вплив» та «акмеологічний супровід»; зазначено основні завдання забезпечення акмеологічного впливу та супроводу на рівні системи психолого-педагогічної підготовки, рівні педагогічного процесу та рівні педагогічної ситуації; запропоновано шляхи реалізації визначених завдань. EN: In the article there have been offered the solution of the problem of projecting of acmeological educational space; acmeological influence and accompaniment of psychological and pedagogical training of future professional and technical educational establishments’ teachers have been theoretically grounded. There have been given the essence of the notions «acmeological influence» and «acmeological accompaniment» which reflect the direction to progressive development of personality on the way to optimum thanks to teacher’s active activity. The author has defined the main tasks of providing the acmeological influence and accompaniment on the level of the system of psychological and pedagogical training (gives necessary strategy in achievement of psychological and pedagogical competence of future professional and technical educational establishments’ teachers); levels of pedagogical process (gives algorithm of actions in achievement the results of mastering the theoretical knowledge, practically oriented and independent activities of some theme and discipline generally) and level of pedagogical situation (contributes optimal concentration of the influence on personality of future professional and technical educational establishments’ teachers). There have been offered the ways of realization of definite tasks as for components of psychological and pedagogical training of future professional and technical educational establishments’ teachers: objective, value-motivate, content, operative-activity, control-regulative and value-productive. The realization of the giving condition contributes the opening the internal potential of students’ personality, development of features and qualities, which contribute to achievements of own optimums in mastering the psychological and pedagogical competence.
Psychological and pedagogical training of future professional and technical educational establishments’ teachers: acmeological aspects
Keywords: акмеологічний вплив; акмеологічний супровід; психолого-педагогічна підготовка; acmeological influence; acmeological accompaniment; psychological and pedagogical training